THE INFLUENCE OF HOUSING ENVIRONMENT ON CONSUMER PREFERENCE AT GRIYA PANIKI INDAH MANADO - Mambu, Michelle Mariana (FEB Universitas Sam Ratulangi Manado, 2014)
Housing is perminant need of people, because of importance for having a proper place to stay. The criteria of a proper house consist of a well-designed environment and quality of product. Since the earliest development of civilization until this era, housing is still becoming one prosperous business concept for many corporate business entrepreneurs. This research is conducted in Manado.The objectives are to analyze influence of housing environment on consumer preference, partially and simultaneously. This research is the causal type of research where it investigate the influence of elements on consumer preference. Use multiple regression models to answer the research problem. The population in this study is a consumers of Griya Paniki Indah, and 98 respondents as its sample. The hypothesis testing, this research conduct a conclusion of there is a significant influence of Mobility, Community Facility, Community Social Capital, Sound Infrastructure, and Quality Product partially and simultaneously. This study reveals that Community Facility is a mental decision that made by the consumer has a strong influence factor in order to buy a house, when consumer go for purchasing, they prefer to purchase house that have social facilities, and became the better environment. Keywords: housing environment, consumer preference, community facility.